A convenient route to mixed cationic group 13/14/15 compounds. Issue 9 (26th January 2023) - Ackermann, Matthias T.; Seidl, Michael; Grande, Riccardo; Zhou, Yuqiao; Ferguson, Michael J.; Timoshkin, Alexey Y.; Rivard, Eric; Scheer, Manfred
Abstract : Reactivity studies on the complex IDipp·GeH2 BH2 OTf with different pnictogenylboranes were carried out. Hereby, unprecedented cationic group 13/14/15 compounds containing chains of only hydrogen-substituted 13/14/15 elements could be obtained. Abstract : The formation of novel cationic mixed main group compounds is reported revealing a chain composed of different elements of group 13, 14, and 15. Reactions of different pnictogenylboranes R2 EBH2 ·NMe3 (E = P, R = Ph, H; E = As, R = Ph, H) with the NHC-stabilized compound IDipp·GeH2 BH2 OTf (1 ) (IDipp = 1, 3-bis(2, 6-diisopropylphenyl)imidazole-2-ylidene) were carried out, yielding the novel cationic, mixed group 13/14/15 compounds [IDipp·GeH2 BH2 ER2 BH2 ·NMe3 ] + (2a E = P; R = Ph; 2b E = As; R = Ph; 3a E = P; R = H; 3b E = As; R = H) by the nucleophilic substitution of the triflate (OTf) group. The products were analysed by NMR spectroscopy and mass spectrometry and for 2a and 2b also by X-ray structure analysis. Further reactions of 1 with H2 EBH2 ·IDipp (E = P, As) resulted in the unprecedented parent complexes [IDipp·GeH2 BH2 EH2 BH2 ·IDipp][OTf] (5a E = P; 5b E = As), which were studied by X-ray structure analysis, NMR spectroscopy and mass spectrometry. Accompanying DFT computations give insight into the stability of the formed products with respect to their decomposition.